2015
DOI: 10.3892/mco.2015.694
|View full text |Cite
|
Sign up to set email alerts
|

One-step nucleic acid amplification assay for intraoperative prediction of advanced axillary lymph node metastases in breast cancer patients with sentinel lymph node metastasis

Abstract: The one-step nucleic acid amplification (OSNA) assay is used to semiquantitatively measure the cytokeratin (CK)19 mRNA copy numbers of each sentinel lymph node (SLN) in breast cancer patients. The aim of the present study was to evaluate whether the diagnosis of ≥4 LN metastases is possible using the OSNA assay intraoperatively. Between May, 2010 and December, 2014, a total of 134 patients who underwent axillary lymph node dissection (ALND) of positive SLNs were analyzed. The total tumor load (TTL) was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, the majority of these prediction models were constructed using predictors derived from breast resection specimen pathology, such as lymphovascular invasion, and have not been widely adopted as they fail to confidently facilitate one-stage intraoperative decision making about the role of ALND. A small number of studies have reported on the prediction of NSLN metastases in SLN-positive patients, including the use of SLN OSNA TTL ( 7 , 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of these prediction models were constructed using predictors derived from breast resection specimen pathology, such as lymphovascular invasion, and have not been widely adopted as they fail to confidently facilitate one-stage intraoperative decision making about the role of ALND. A small number of studies have reported on the prediction of NSLN metastases in SLN-positive patients, including the use of SLN OSNA TTL ( 7 , 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kubota et al ( 18 ) reported a single-centre standardised method for SLN detection that used indocyanine green; whereas, the types of injection and the use of radioisotope, with or without dye, varied according to institutional practice in a multi-centre study by Piñero-Madrona et al ( 19 ). The present single-centre dual technique of SLN detection is uniform and standardised ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Banerjee et al produced a stratified TTL cutoff of avoiding ALND if TTL < 1400 copies and proceeding with ALND if TTL > 7500 copies with the intermediate group depending on the degree of lymphovascular invasion 9 . Kubota et al 12 examined the correlation of TTL with having more than four positive lymph nodes and identified a cutoff of 54 000 copies (sensitivity 74%; specificity 59%). Shimazu et al 15 have shown TTL to be both significantly associated with higher nodal involvement as well as the presence of four or more positive nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, OSNA can be predictive of four node involvement with a copy number of >100 000 copies/µL 7 and total tumor load (TTL—total of copy numbers in submitted nodes) can be used to differentiate patients using Z0011 criteria 8 . TTL has proven a focus of research with multiple studies showing it to be an independent predictor of higher nodal involvement 9‐12 …”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, many researchers are keen to apply molecular assays to improve intra-operative pathologic accuracy of breast SLNs, such as the Metasin assay [ 18 , 19 ] and one-step nucleic acid amplification assay (OSNA) [ 20 , 21 ], but neglect to give full consideration to the existing mature pathologic techniques (TIC and FS), which are widely used in clinical practice. In addition, a study of OSNA in 552 patients showed both OSNA and TIC can serve as qualified intra-operative assessments of SLNs, and suggested that OSNA can be applied as a complement to histopathologic assessment, but cannot replace pathology with serial sectioning [ 22 ].…”
Section: Discussionmentioning
confidence: 99%